Ekonomiczne i społeczne następstwa globalizacji - Kaczmarek, Bartłomiej (Annales. Etyka w Życiu Gospodarczym, 2014)
The subject of this article in an analysis of the globalisation processin economic and social areas. The author describes the main spheresof globalisation such as economic and political integration, the declining roleof nation states, cultural homogenisation and the increasing significanceof transnational corporations. The advantages and disadvantages of globalisationare discussed. The author also indicates differences between regions that benefitfrom globalisation. The article tries to answer questions whether globalisationis a desirable process and what it should be like to bring more benefits than losses.